Adipogenic and Osteogenic Markers Characterization of Human Amniotic Fluid Stem Cells - Hassan IH El-Sayyad; Mohamed A Sobh; Soad A Khalifa; Omnia KRA El-Sayyad (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2016)
Objective: Human amniotic fl uid stem cells (HAFSCs) derived from human amniotic fl uid during parturition are of good source in regenerative medicine for development to either adipocyte, chondrogenic or osteogenic cells. Methods and results: The HAFSCs were obtained from amniotic fl uid post-parturition. A written informed consent had been taken beforehand from mothers after parturition during admission in Mansoura  University Hospital, Egypt. Cultured in adipogenic or osteogenic culture for 4,7,14 & 21 days. Flow cytometry of HAFSCs for Oct-4, CD13,, CD29 , CD 90 , CD34 and CD 14. Gene expression for  adipogenic (PCR of leptin, peroxisome proliferator-activated receptor-γ and lipoprotein lipase) and  osteogenic (osteocalcin) cells were carried out. Biochemical assessments of adipogenic (lipoprotein lipase enzyme and glycerol-3-phosphate dehydrogenase) and osteogenic (alkaline phosphatase,  B-galactosidase and calcium content) markers. HAFSCs were positive for Oct-4, CD13,, CD29 , CD 90 and negative CD34 and CD 14. Also, light and transmission electron microscopic investigation of adipocyte stem cell culture were investigated at 4,7,14 & 21 days in both two models. Adipocyte derived from HASCs displayed fibroblastic morphology and confluence at 7 days and fl at-shape with positive oil red staining at 14 &21 days. At ultrastructural level, the adipocyte derived from HASCs exhibited ideal structure. Also, it showed adipogenic gene expression and biochemical investigation. Similar was  observed of its osteogenic affi nity of bone cells derived from HFASCs. Conclusion: The authors concluded that HAFSCs are capable of differentiating into adipocyte,  osteoblast and chondroblast depending on the culture medium and are important in regenerating medicine.